PROCEDURAL LIABILITY IN CRIMINAL AND ADMINISTRATIVE PROCEEDINGS: INTEGRATION PROSPECTS - SPIRIDONOV Mikhail Sergeevich (Правовое государство: теория и практика)
The institution of procedural liability as a means of protecting procedural law has been formed to some extent in almost every procedural branch of law. At the same time, branch types of procedural liability have both individual features characteristic of a particular branch of law and general features inherent in this legal phenomenon as a whole. The main attention of researchers of procedural liability is directed precisely at problematic issues within individual procedural branches. At the same time, procedural liability is of special interest from the point of view of interbranch research, because such an approach on the basis of the revealed branch regularities of existence of this legal institution allows to develop its general basic principles and standards, to unify the conceptual apparatus, to develop measures to improve the legislation and judicial practice. This determines the relevance of this study. Purpose: to carry out a comparative interbranch analysis of the institution of procedural liability from the positions of doctrinal and law enforcement approaches. Methods: the methodological basis of the study is the unity of universal, general scientific and special-legal methods of legal science, including abstract-logical, comparative-legal, formal-legal, structural-functional. Results: the article reveals general approaches to the definition of the concept and content of procedural liability in such branches of law as criminal procedure and administrative procedure. Based on the analysis of legislation, legal positions of the Plenum of the Supreme Court of the Russian Federation and examples of judicial practice, the article substantiates the position that there are sufficient prerequisites for convergence and unification of the institution of procedural liability in criminal and administrative proceedings. On the basis of the fact that in criminal and administrative proceedings the issue of competition between procedural and substantive types of liability is solved in a similar way, the article concludes that it is necessary to develop problems of such significance precisely at the interbranch level.